EVALUASI SARANA DAN PRASARANA LABORATORIUM IPA SMA KABUPATEN PADANG PARIAMAN - El Basthoh; Najmi Hayati (STKIP Pesisir Selatan, 2020)
This study aims to evaluate the facilities and infrastructure of senior high school science laboratory in Padang Pariaman Regency. Senior high school 1 Lubuk Alung. Senior high school YDB Lubuk Alung, Senior high school 1 Kayu Tanam,Senior high school 2 Lubuk Alung and Senior high school 1 Batang Anai. Data collection techniques through questionnaire / questionnaire instruments used to reveal data about laboratory facilities and infrastructure. Based on theanalysis of the data it was found that the state of the laboratory in terms of facilities and infrastructure at five schools in Padang Pariaman Regency was in the fairly complete category.